Caring Behaviors Inventory-24: translation, cross-cultural adaptation, and psychometric testing for using in nurses and patients - Neda Azimi Khaletabad; Moloud Radfar; Mojgan Khademi; Hamidreza Khalkhali (BMC, 2023)
Abstract Background To measure caring behaviors, it is necessary to have an instrument adapted based on the contextual culture. This study aimed to translate Caring Behaviors Inventory-24 (CBI-24) into Persian and determine its psychometric properties. Methods This is a methodological study conducted to translate and then psychometrically test The CBI-24. The forward-backward translation was conducted using the World Health Organization (WHO) model and Wild et al. (2005) approach. The face, content, and construct validity of the inventory were assessed using cognitive interviews (10 nurses and 10 patients), expert panel deliberations (10 experts), and the exploratory and confirmatory factor analyses (300 nurses and 300 patients), respectively. The reliability was determined using the internal consistency (300 nurses and 300 patients) and test-retest method (30 nurses and 30 patients). Results After translating the CBI-24 and combining its items, the forward translation was initially conducted and the final backward translation was then sent to the developer for confirmation. The final version of the inventory was prepared after the completion of cognitive interviews. The content validity index of all items was reported to be more than 0.8 and good. The Cohen's kappa coefficient of all items was also shown to be higher than 0.74 and excellent. The factor loading of all items except item 19 was above 0.3. Item 19 was removed since it caused the alpha value of the respectfulness dimension to be 0.32. The Cronbach's alpha and the correlation coefficient of the whole inventory were calculated to be 0.95 and 0.88, respectively. Conclusion The Persian version of CBI-24 can be a suitable tool for measuring caring behaviors among patients and nurses.